PENDAMPINGAN BELAJAR PENDIDIKAN FORMAL SANTRI TAMAN PENDIDIKAN AL QUR’AN - Faza Khoirul Muna; Novi Andriani; Titis Rosowulan (khidmatan, 2024)
This community service program aims to address the difficulties in formal academic mentoring experienced by students (santri) of TPQ (Qur'anic Education Center) Roudlotul Athfal in Tidaran 1 Hamlet. The limited time available to parents, who predominantly work as farmers and laborers, created a gap between the demands of formal schooling and the necessary learning support at home. The methodology employed was the Asset Based Community Development (ABCD) approach, which began with a Focus Group Discussion (FGD) to identify community needs and aspirations. Using the ABCD framework, the hamlet's primary asset—its educated youth—was identified as the key solution. The resulting intervention was a structured tutoring program implemented under the auspices of TPQ Roudlotul Athfal, with a synchronized schedule designed not to interfere with religious study sessions. The program successfully provided intensive academic guidance, enhanced the students' knowledge and self-reliance, while simultaneously developing the teaching skills and sense of social responsibility among the local youth, which is crucial for the program's sustainability.